Umbilical bleeding during menstruation in status post laparoscopic cholecystectomy of unknown/ambiguous aetiology - Mannan, Ambreen Abdul; Soomro, Suhail Ahmed; Kumari, Aneeta; Memon, Fauzia Abdul Raheem (International Surgery Journal, 2022)
Although umbilical endometriosis is a possible cause of cutaneous manifestation of retrograde menstruation during cyclical bleeding in status post laparoscopic surgery patient, Here in this case we presumed a diagnosis of endometriosis on the basis of its symptoms which couldn’t be proven in biopsy and on immune-histo-chemistry and casted a query that now what is the next possible aetiology which is responsible for umbilical bleeding specifically during menstruation in the patient with status post laparoscopic surgery. We report a case of presumed secondary umbilical port scar endometriosis in a 25-year-old lady nulliparous woman following laparoscopy-assisted cholecystectomy 6 months ago. Remarkably patient complained of peri umbilical pain and menstrual bleeding through umbilicus (retrograde) soon after surgery which was remarkably noticed only during her periodical cycle. History and clinical examination, haematology, ultrasound, computed tomography and MRI of abdomen and pelvis performed to rule out any primary lesions which all were found unremarkable. After counselling the patient about the presumptive causes and treatment options the umbilicus with its surgical scar mark excised and the tissue was sent for histopathological examination which was found inconclusive with no evidence of endometriosis at all. Remarkably it was further scrutinized by immune-histo-chemistry but remained fruitless. Fortunately, patient relieved her symptoms of retrograde menstrual bleeding after total excision of the umbilicus with scar mark post operatively but still left a diagnostic stigma for surgeons.